Integrated biorefineries : design, analysis, and optimization - Stuart, Paul R.; El-Halwagi, Mahmoud M., 1962- (Green chemistry and chemical engineering., 2013)
Integrated Biorefineries: Design, Analysis, and Optimization examines how to create a competitive edge in biorefinery innovation through integration into existing processes and infrastructure. Leading experts from around the world working in design, synthesis, and optimization of integrated biorefineries present the various aspects of this complex process, capturing the state of the art in the advancing bioeconomy. The book defines an integrated biorefinery as a processing facility that transforms biomass into value-added products-from biofuels and biochemicals to food and pharmaceuticals. The.